2015
DOI: 10.1186/s13223-015-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective case note review of chronic spontaneous urticaria outcomes and adverse effects in patients treated with omalizumab or ciclosporin in UK secondary care

Abstract: BackgroundOmalizumab is approved in the UK as add-on treatment for chronic spontaneous urticaria (CSU) in patients with inadequate response to H1-antihistamines. Ciclosporin is an established but unlicensed 3rd line option for CSU. Two parallel retrospective observational studies were conducted to describe outcomes of treatment and adverse events with omalizumab or ciclosporin for CSU treatment.MethodsData from UK specialist centres prescribing omalizumab (five centres) or ciclosporin (three centres) in CSU p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
45
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 17 publications
9
45
2
4
Order By: Relevance
“…[20] przeprowadzili retrospektywną analizę porównawczą pacjentów z pokrzywką przewlekłą nieodpowiadających na terapię lekami przeciwhistaminowymi leczonych omalizumabem i cyklosporyną. U pacjentów otrzymujących omalizumab stwierdzono istotnie większą poprawę jakości życia mierzoną jako redukacja wskaźnika wpływu dolegliwości skórnych na jakość życia (ang.…”
Section: Omalizumabunclassified
“…[20] przeprowadzili retrospektywną analizę porównawczą pacjentów z pokrzywką przewlekłą nieodpowiadających na terapię lekami przeciwhistaminowymi leczonych omalizumabem i cyklosporyną. U pacjentów otrzymujących omalizumab stwierdzono istotnie większą poprawę jakości życia mierzoną jako redukacja wskaźnika wpływu dolegliwości skórnych na jakość życia (ang.…”
Section: Omalizumabunclassified
“…The most common adverse events associated with the use of CsA include hypertension, fatigue, gastrointestinal problems, and headache [15]. It is also thought that long-term use of CsA may be responsible for the development of non-melanoma skin cancer [16].…”
Section: Cyclosporin Amentioning
confidence: 99%
“…Cyclosporin has been reported to be efective in some studies of CSU, including three double-blind [12][13][14][15][16][17][18], and one study reported that 40% of patients achieved complete remission in 9 months [18].…”
Section: Cyclosporin Amentioning
confidence: 99%
“…[2][3][4]16,171 Ainda assim, a razão risco/benefício tem mostrado ser bastante superior à utilização de corticóides a longo prazo. 1,138 Dado o expectável aumento de efeitos adversos com o tempo de utilização, alguns autores recomendam este tratamento apenas por três meses, 16 mas outros utilizam a ciclosporina em tratamentos mais longos, [139][140][141][142] havendo mesmo recomendações para tratamentos prolongados quando necessário. 143 As várias opções de recomendação descritas na literatura são: a) adição de ciclosporina a um anti-H1 de segunda geração, como opção de terceira linha, apenas em doentes com urticária grave e refratária a qualquer dose de anti-histamínicos 1 ; b) apenas utilizar ciclosporina A após falha de resposta ao omalizumab 16,17 ; ou c) considerar ciclosporina em baixa dose em doentes com urticária grave e refractária a anti-histamínicos.…”
unclassified
“…52,155,156 Não existem comparações diretas entre o omalizumab e a ciclosporina, possivelmente dada a reconhecida dife-rença entre os perfis de segurança destes dois fármacos. No entanto, das três comparações indiretas encontradas, dois estudos concluem que o omalizumab é superior à ciclosporina em eficácia, 141,154 enquanto um conclui que a eficácia é semelhante, mas o perfil de segurança da ciclosporina é inferior.…”
unclassified